The Mechanism of Religious Tolerant Formation through Integrated Curriculum Pesantren of Darul Istiqomah for Female Campus Bondowoso - Abu Darda; Rosendah Dwi Maulaya; Dinni Izzati; Nurul Salis Alamin; Assyifa Qori Lhegina (IJECA (International Journal of Education and Curriculum Application), 2026)
Tolerance serves as an essential foundation within the plurality of global society; however, contemporary social realities continue to exhibit complex challenges, including discrimination and intolerant narratives that erode social cohesion. Religious educational institutions, specifically Pesantren, play a pivotal role in mitigating these issues through the strategic internalization of spiritual values. This study aims to analyze the mechanisms of internalizing tolerance values among students at Pesantren of Darul Istiqomah for Female Campus, Bondowoso. Some existing studies have not answered how women's Pesantren internalize the character of tolerance. So, this study seeks to fill the gap. Adopting a qualitative descriptive method with a case study approach, data were gathered through observation, in-depth interviews with institutional authorities (the Director of TMI, caregivers, and teachers), and documentation. The data were subsequently analyzed using the Miles and Huberman model. The findings reveal that the cultivation of a tolerant character is executed through three integrated pathways: curricular (classroom instruction), co-curricular (supervised night study), and extracurricular (independent activities and organizational mandates). Furthermore, the 24-hour dormitory system acts as a primary catalyst in fostering spiritual discipline and social sensitivity among students. The implications of this research underscore that a holistic, Pesantren-based educational model which integrates formal instruction with controlled residential life effectively produces moderate individual profiles. This study offers a theoretical contribution to the development of character education curricula as a response to the global crisis of tolerant through a value-based pedagogical approach.